Histopathological changes in the trabecular meshwork in primary congenital glaucoma - Aparna Rao (American Journal of Ophthalmology Case Reports)
Purpose: To evaluate the morphological changes in the ex-vivo trabecular meshwork TM specimens from patients with primary congenital glaucoma. Methods: Five trabecular meshwork (TM) specimens obtained after microincisional trabeculectomy from 4 patients with primary congenital glaucoma (mean age) were analyzed using hematological and eosin staining. Results: The trabecular meshwork in PCG showed an expansion of the juxtacanalicular and corneoscleral meshwork regions with increased cellularity, thickened TM beams, prominent spindle-shaped nuclei suggesting epithelial mesenchymal transformation predominantly and two morphologically distinct zones of the juxtacanalicular region. Conclusions: Increased cellularity, zonal expansion and mesenchymal changes in specific TM regions suggest aberrant differentiation and differential dysgenesis of different TM regions in PCG.